A catalytic moment: The Greek crisis in the German financial press. (July 2014) - Kutter, Amelie
The Greek crisis has attracted more public-political attention than any other sovereign debt crisis within the European Union. This article investigates the argument that this is due to the symbolic-catalytic role that the Greek crisis played in forging a specific approach to state rescue and the reform of the European Economic and Monetary Union (EMU). Drawing on assumptions of interpretive-narrative political studies about the discursive construction of crisis and a Critical Discourse Analysis of editorials from the financial press, the study shows how this approach was 'catalyzed' by a specific construction of the 'Greek case'. Reference to the 'Greek case', in particular the high level of government debt, rendered austerity a plausible option of crisis management. Reference to the contagion potential of the Greek crisis justified the application of austerity across the Eurozone. The Greek crisis was also seen to reveal the systemic flaws of the EMU and suggest deepened economic integration.